Penerapan Model Pembelajaran Kooperatif Tipe Make A Match untuk Meningkatkan Aktivitas Belajar Siswa pada Pembelajaran Pendidikan Pancasila di SMA Negeri 13 Medan - Zain, Rahmita Firda; Kesuma, Sapta; Muslim, Yusnita (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to increase student learning activities with the Make A Match learning model at SMAN 13 Medan. The research subjects were 36 class X.3 students. Data was collected through observation using observation sheets and documentation. The data analysis technique used is quantitative descriptive. The research results show that the Make A Match cooperative learning model is effective in increasing student activity. This is evidenced by the increase in student learning activity, where in cycle I, 52.2% of students reached the level of active learning, this percentage increased to 79% in cycle II. The score increased by 26.5%. The average score of student observations in cycle I and cycle II was 71.6%. Based on this explanation, it can be concluded that the Make A Match type cooperative learning model has the potential to increase the learning activities of PPKn students in class X.3 of SMA Negeri 13 Medan for the 2024/2025 academic year